Method for improving content and distribution uniformity of filler in paper sheet and increasing strength of paper sheet

By preparing modified composite nanofiber dispersion and a positive composite sustained release solution, combined with the mixed production technology of grinding calcium carbonate and papermaking pulp, the problems of uneven distribution of fillers in paper and the decrease in paper strength are solved, and high filler content, uniform distribution and paper page strength are achieved.

CN119777199AActive Publication Date: 2025-04-08山东奥赛新材料有限公司

Patent Information

Application Number
CN202510292982.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-03-13
Publication Date
2025-04-08
Estimated Expiration
2045-03-13

AI Technical Summary

Technical Problem

During the papermaking process, the distribution of fillers in the Z direction of the paper cross-section is uneven, resulting in deterioration of the mechanical properties, surface quality and stability of the paper. At the same time, increasing the amount of fillers to increase the filler content will lead to a decrease in paper strength.

Method used

By preparing modified composite nanofiber dispersion, positive buffer, positive composite sustained release solution and filler particle suspension, the gradient positive composite sustained release solution is mixed with grinded calcium carbonate to form a uniform filler particle suspension and mixed with the paper pulp to improve the distribution uniformity and strength of the filler in the paper page.

Benefits of technology

It is achieved to improve the filler content in the paper sheet while improving the uniformity of the filler distribution, and effectively avoid the adverse effects of the increase in the filler usage on the mechanical properties of the paper sheet, thereby improving the strength of the paper sheet.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
  • Figure SMS_2
    Figure SMS_2
  • Figure SMS_3
    Figure SMS_3
Patent Text Reader

Abstract

The invention provides a method for increasing the content and distribution uniformity of filler in paper sheets and increasing the strength of the paper sheets, and belongs to the technical field of papermaking. The method for improving the content and distribution uniformity of the filler in the paper sheet and increasing the strength of the paper sheet comprises the following steps: preparing a modified composite nanofiber dispersion liquid, preparing a positive electric buffer solution, preparing a positive electric composite slow release solution, preparing a filler particle suspension liquid, and mixing and manufacturing paper with pulp. According to the method for improving the content and the distribution uniformity of the filler in the paper sheet and improving the strength of the paper sheet, the flocculation speed of the filler can be mildly and effectively controlled, the size of floccules can be controllably adjusted, the distribution uniformity of the filler in the paper sheet can be improved while the content of the filler in the paper sheet is improved, and the paper sheet strength is improved. The adverse effect on the mechanical property of the paper sheet caused by filler dosage increase is effectively avoided, and the paper sheet strength is further improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of papermaking, and in particular to a method for increasing filler content and distribution uniformity in paper sheets and increasing the strength of paper sheets. Background Art

[0002] In the papermaking process, adding fillers (such as calcium carbonate, talcum powder, titanium dioxide, etc.) is one of the key steps to optimize paper performance. Adding fillers can not only replace part of the fiber raw materials, reduce fiber usage, and reduce production costs, but also give paper certain properties, such as filling the gaps between fibers in the paper, improving paper uniformity and smoothness, enhancing paper opacity and whiteness, and improving printability. Among them, fillers fill the gaps between fibers in paper by embedding into the pores between fibers through the filling effect of fillers, thereby improving the density of the paper structure and improving the physical properties of paper; fillers improve the uniformity and smoothness of paper by reducing the "bridging" phenomenon between fibers and reducing surface unevenness through the filling effect of fillers, thereby improving the uniformity and smoothness of paper; fillers improve the opacity and whiteness of paper by scattering, refracting and absorbing light after the fillers are filled in the paper, causing the light to scatter and refract at the interface between the fillers and the fibers, reducing the proportion of transmitted light, and adjusting the original light yellow tone of the fibers through the fillers' own color tone, thereby achieving the aforementioned functions; fillers improve the printability of paper by improving the surface flatness of the paper after filling the gaps between fibers, and combining the fillers' absorption and fixation effects on printing inks to reduce "dot loss" during printing and improve image clarity.

[0003] However, adding fillers also has adverse effects on the paper itself. Specifically, during the dehydration process of the papermaking net, under the influence of gravity and vacuum suction, the fillers will move down rapidly with the white water, resulting in a large number of filler particles gathering near the back of the paper web (i.e., near the forming net) and relatively few near the front of the paper web (i.e., far away from the forming net) in the Z direction of the paper cross section. The distribution of fillers in the Z direction of the paper cross section is uneven, which directly leads to the deterioration of the mechanical properties, surface quality, stability, etc. of the paper. At the same time, in order to improve the distribution of filler particles near the front of the paper web, if the amount of filler is directly increased to increase the filler content in the paper sheet, the strength of the paper will be significantly reduced, and the two are negatively correlated; while increasing the filler content of the paper, avoiding the loss of paper strength is a technical problem in the field of papermaking.

[0004] The prior art discloses that filler particles are pretreated with anionic sodium polyacrylate, and then flocculated with a high molecular weight flocculant such as cationic starch and guar gum flocculant, and then combined with dimethylaminoethyl methacrylate and acrylamide copolymer to form a filler floc; the filler floc is mixed with raw pulp to increase the amount of filler added to the paper. However, in actual production, the coating effect of the coagulant used on the filler particles is not easy to control: when the amount of coagulant added is small, the flocs formed by the filler particles are small, and the flocculation effect is not obvious; thus, the amount of filler added to the paper is not significantly increased, and the filler content in the paper is not significantly increased. When the amount of coagulant added is large, due to the large molecular weight of the positively charged flocculant component and its strong positive charge, the filler particles will be quickly coated in large quantities, and super-large filler flocs will be formed locally, which will lead to a more uneven distribution of the filler in the paper; what is more, when the filler flocculates into super-large flocs, filler spots will be formed in the paper, affecting the physical properties and printing properties of the paper, resulting in substandard product quality. Summary of the invention

[0005] In order to solve the technical problems existing in the prior art, the present invention provides a method for increasing the filler content and distribution uniformity in paper sheets and increasing the strength of paper sheets. The method can gently and effectively control the filler flocculation speed and controllably adjust the floc size. The method can increase the filler content in the paper sheets while improving the distribution uniformity of the filler in the paper sheets, and effectively avoid the adverse effects of increased filler dosage on the mechanical properties of the paper sheets, thereby further improving the strength of the paper sheets.

[0006] In order to solve the above technical problems, the technical solution adopted by the present invention is as follows: A method for increasing the filler content and distribution uniformity in a paper sheet and increasing the strength of the paper sheet, comprising the following steps: preparing a modified composite nanofiber dispersion, preparing a positively charged buffer, preparing a positively charged composite slow-release liquid, preparing a filler particle suspension, and mixing and papermaking; The preparation of the modified composite nanofiber dispersion comprises the following steps: pre-compounding and modification treatment; The pre-compounding comprises dispersing carboxymethyl cellulose nanofibers in deionized water to obtain a nanofiber dispersion; dropping a zinc nitrate aqueous solution into the nanofiber dispersion, heating the solution to 35-40° C., and dropping a 2-methylimidazole aqueous solution; keeping the solution warm for reaction, allowing the solution to stand, separating and obtaining a solid, and washing and drying the solid to obtain composite nanofibers; In the modification treatment, the composite nanofibers are treated with a positively charged modification liquid to obtain a modified composite nanofiber dispersion; The positively charged modification liquid is an aqueous solution of dimethyldiallylammonium chloride; The preparation of the positively charged buffer comprises reacting acrylamide, dimethyldiallyl ammonium chloride and 3-acryloylpropyltrimethylammonium chloride at elevated temperature in the presence of an initiator to obtain a positively charged buffer; The method for preparing the positively charged composite sustained-release liquid comprises uniformly mixing the modified composite nanofiber dispersion, the positively charged buffer solution and the amphoteric high molecular weight polyacrylamide to obtain the positively charged composite sustained-release liquid.

[0007] Furthermore, in the preparation of the filler particle suspension, the ground calcium carbonate is added into deionized water to obtain a ground calcium carbonate dispersion; the positively charged composite slow-release liquid is added to the ground calcium carbonate dispersion to obtain a filler particle suspension; In the mixed papermaking, the papermaking pulp and the filler particle suspension are uniformly mixed and then diluted, and a retention agent is added before papermaking to obtain base paper.

[0008] Preferably, in the pre-compounding, the mass concentration of the nanofiber dispersion is 2.9-3.3wt%; The concentration of zinc nitrate aqueous solution is 0.2-0.3 mol / L; The concentration of 2-methylimidazole aqueous solution is 0.4-0.6 mol / L; The heat preservation reaction time is 10-12h, and the standing time is 6-8h.

[0009] Preferably, in the pre-compounding, the weight ratio of the carboxymethyl cellulose nanofibers in the nanofiber dispersion to the zinc nitrate in the zinc nitrate aqueous solution is 5-5.5:1; The molar ratio of zinc nitrate in the zinc nitrate aqueous solution to 2-methylimidazole in the 2-methylimidazole aqueous solution is 1:4-4.2.

[0010] Furthermore, the modification method is to disperse the composite nanofibers in deionized water to obtain a composite nanofiber dispersion with a mass concentration of 8-8.5wt%; then drip a positively charged modification liquid with a mass concentration of 11-12wt%, treat at room temperature, and obtain a modified composite nanofiber dispersion.

[0011] Preferably, in the modification treatment, the treatment time at room temperature is 4-5h; The weight ratio of the composite nanofibers in the composite nanofiber dispersion to the dimethyldiallylammonium chloride in the positively charged modification liquid is 1:0.28-0.31.

[0012] Furthermore, the method for preparing the positively charged buffer is to disperse acrylamide, dimethyldiallyl ammonium chloride, and 3-acryloylpropyltrimethylammonium chloride in deionized water to obtain a mixed monomer solution with a monomer mass concentration of 10-12wt%, add an initiator, and heat the reaction to obtain a positively charged buffer; In the mixed monomer solution, the weight ratio of acrylamide, dimethyldiallylammonium chloride and 3-acryloylpropyltrimethylammonium chloride is 2.3-2.5:0.6-0.7:0.5-0.6.

[0013] Preferably, in the preparation of the positively charged composite sustained-release liquid, the weight ratio of the modified composite nanofiber dispersion, the positively charged buffer, and the amphoteric high molecular weight polyacrylamide is 1-1.2:1-1.2:2.9-3.1.

[0014] Preferably, in the preparation of the filler particle suspension, the mass concentration of the ground calcium carbonate dispersion is 30-33wt%; The added weight of the positive charge composite sustained-release liquid is 0.1-2% of the weight of the ground calcium carbonate in the ground calcium carbonate dispersion.

[0015] Preferably, in the mixed papermaking, the absolute dry weight ratio of the ground calcium carbonate in the filler particle suspension to the papermaking pulp is 30-50%:50-70%.

[0016] Compared with the prior art, the present invention has the following beneficial effects: (1) The method of increasing the filler content and distribution uniformity in paper sheets and increasing the strength of paper sheets of the present invention comprises the following steps: a gradient positively charged composite slow-release liquid containing small molecular weight, medium molecular weight and high molecular weight is prepared, mixed with ground calcium carbonate to form a filler particle suspension, and then mixed with papermaking pulp for papermaking; wherein the ground calcium carbonate is in contact with the positively charged composite slow-release liquid, and the small molecular weight modified composite nanofibers in the positively charged composite slow-release liquid are positively charged and have a small molecular weight, good mobility and flexibility, and can preferentially contact the filler particles, thereby reducing the negative charge of the filler particles and being able to be more warm. and flocculate with the negatively charged filler particles; at the same time, the combination of medium molecular weight cationic modified polyacrylamide polymer (i.e. positively charged buffer) can effectively buffer the flocculation rate of high molecular weight polyacrylamide and filler particles, effectively avoid the formation of super large flocs, and effectively control the size of filler flocs and their uniform distribution in papermaking pulp; at the same time, the modified composite nanofibers have the characteristics of large specific surface area, many chemical bonds, high surface energy and high activity, and have strong bonding with fillers and pulp fibers, and can form a more solid fiber network structure, thereby effectively improving the strength of paper sheets. Furthermore, the medium molecular weight cationic modified polyacrylamide polymer (i.e., cationic buffer) of the cationic composite sustained-release liquid has stronger cationicity and larger molecular weight than the small molecular weight modified composite nanofibers, and can achieve further buffering effect on its basis; by combining the small molecular weight modified composite nanofibers and the medium molecular weight cationic modified polyacrylamide polymer, the Z-direction distribution uniformity of cellulose fibers and filler flocs in the paper can be improved, the filler content in the paper sheet can be increased, and the strength of the paper sheet can be simultaneously improved under the condition of high filler content; the aforementioned technical means cooperate with each other and work synergistically, which can gently and effectively control the filler flocculation speed, controllably adjust the floc size, and can improve the filler content in the paper sheet while improving the distribution uniformity of the filler in the paper sheet, and effectively avoid the adverse effects of increased filler dosage on the mechanical properties of the paper sheet, thereby further improving the strength of the paper sheet.

[0017] (2) The method of increasing the filler content and distribution uniformity in paper sheets and increasing the strength of paper sheets of the present invention controls the absolute dry weight ratio of filler to paper pulp to be 35%:65%, and the basis weight obtained by papermaking is 180g / m 2 White cardboard, the bursting index can reach 2.47 (kPa·m 2 ) / g, the longitudinal Taber stiffness can reach 4.91mN·m, the transverse Taber stiffness can reach 3.17mN·m, the transverse folding endurance can reach 119 times, and the ash content can reach 25.4%.

[0018] (3) The method of increasing the filler content and distribution uniformity in paper sheets and increasing the strength of paper sheets of the present invention controls the absolute dry weight ratio of filler to papermaking pulp to be 45%:55%, and the basis weight obtained by papermaking is 180g / m 2 White cardboard, the bursting index can reach 2.40 (kPa·m2 ) / g, the longitudinal Taber stiffness can reach 5.52mN·m, the transverse Taber stiffness can reach 3.36mN·m, the transverse folding endurance can reach 113 times, and the ash content can reach 28.6%.

[0019] (4) The method of increasing the filler content and distribution uniformity in paper sheets and increasing the strength of paper sheets of the present invention controls the absolute dry weight ratio of filler to papermaking pulp to be 35%:65%, and the basis weight obtained by papermaking is 70g / m 2 The offset paper has a tensile index of up to 60.61N·m / g, a transverse folding endurance of up to 36 times, a printing surface strength (front side) of up to 3.39m / s, a printing surface strength (back side) of up to 3.30m / s, and an ash content of up to 26.1%.

[0020] (5) The method of increasing the filler content and distribution uniformity in paper sheets and increasing the strength of paper sheets of the present invention controls the absolute dry weight ratio of filler to paper pulp to be 45%:55%, and the basis weight obtained by papermaking is 70g / m 2 The offset paper has a tensile index of up to 69.26 N·m / g, a transverse folding endurance of up to 34 times, a printing surface strength (front side) of up to 3.86 m / s, a printing surface strength (back side) of up to 3.08 m / s, and an ash content of up to 28.0%.

[0021] (6) The method of the present invention for increasing the filler content and distribution uniformity in paper sheets and increasing the strength of paper sheets has strong applicability and can be effectively applied not only to the production of white cardboard but also to the production of offset paper. It can effectively increase the filler content and distribution uniformity in white cardboard and offset paper and increase their strength. DETAILED DESCRIPTION

[0022] In order to have a clearer understanding of the technical features, purposes and effects of the present invention, the specific embodiments of the present invention are now described. It should be noted that the following detailed descriptions are exemplary and are intended to provide further explanation of the present invention. Unless otherwise specified, all technical and scientific terms used in the present invention have the same meanings as those commonly understood by those of ordinary skill in the art to which the present invention belongs.

[0023] It should be noted that the terms used herein are only for describing specific embodiments and are not intended to limit exemplary embodiments according to the present invention. As used herein, "first", "second", etc. are used to distinguish similar objects, and are not used to describe a specific order or sequence. In addition, it should be understood that when the terms "comprising" and / or "including" are used in this specification, it indicates the presence of features, steps, operations, devices, components and / or combinations thereof.

[0024] The embodiment of the present invention provides a method for improving the filler content and distribution uniformity in paper sheets and increasing the strength of paper sheets, which comprises the following steps: preparing a modified composite nanofiber dispersion, preparing a positively charged buffer solution, preparing a positively charged composite sustained-release solution, preparing a filler particle suspension, and mixed papermaking.

[0025] The preparation of the modified composite nanofiber dispersion comprises the following steps: pre-compounding and modification treatment.

[0026] The pre-compounding method comprises the following steps: putting carboxymethyl cellulose nanofibers into deionized water, and ultrasonically dispersing for 20-30 minutes to obtain a nanofiber dispersion with a mass concentration of 2.9-3.3wt%; dripping a zinc nitrate aqueous solution with a concentration of 0.2-0.3 mol / L into the nanofiber dispersion under stirring at room temperature, and continuing to stir for 20-40 minutes after the dripping is completed; then stirring and heating to 35-40° C., keeping the temperature stirred and dripping a 2-methylimidazole aqueous solution with a concentration of 0.4-0.6 mol / L, and controlling the dripping rate of the 2-methylimidazole aqueous solution to be 0.4-0.5 mL / min; after the dripping of the 2-methylimidazole aqueous solution, keeping the temperature stirred for 10-12 hours, and standing for 6-8 hours; then centrifuging to obtain a solid, and washing the solid with deionized water and drying to obtain the composite nanofibers.

[0027] In the pre-compounding, the weight ratio of the carboxymethyl cellulose nanofibers in the nanofiber dispersion to the zinc nitrate in the zinc nitrate aqueous solution is 5-5.5:1; The molar ratio of zinc nitrate in the zinc nitrate aqueous solution to 2-methylimidazole in the 2-methylimidazole aqueous solution is 1:4-4.2; The diameter of carboxymethyl cellulose nanofibers is 50-100 nm.

[0028] The modification treatment method is as follows: adding the composite nanofibers into deionized water, stirring evenly, obtaining a composite nanofiber dispersion with a mass concentration of 8-8.5wt%, and setting it aside; adding dimethyldiallyl ammonium chloride into deionized water, stirring evenly, obtaining a positively charged modified liquid with a mass concentration of 11-12wt%, and setting it aside; at room temperature, under stirring conditions of 200-300rpm, at a dropping rate of 0.9-1mL / min, adding the positively charged modified liquid dropwise to the composite nanofiber dispersion; after the positively charged modified liquid is added dropwise, stirring is continued at room temperature for 4-5h to obtain a modified composite nanofiber dispersion.

[0029] In the modification treatment, the weight ratio of the composite nanofibers in the composite nanofiber dispersion to the dimethyldiallylammonium chloride in the positively charged modification solution is 1:0.28-0.31.

[0030] The method for preparing a positively charged buffer comprises the following steps: adding acrylamide, dimethyldiallyl ammonium chloride and 3-acryloyltrimethylammonium chloride into deionized water, stirring evenly, obtaining a mixed monomer solution with a total mass concentration of 10-12wt% of monomers (acrylamide, dimethyldiallyl ammonium chloride and 3-acryloyltrimethylammonium chloride) for standby use; adding ammonium persulfate into deionized water, stirring evenly, obtaining an ammonium persulfate solution with a mass concentration of 1-1.2wt%, for standby use; adding the mixed monomer solution and the ammonium persulfate solution into a reaction kettle, heating to 55-60°C under stirring at 150-250rpm, and stirring for 3-4h to obtain a positively charged buffer.

[0031] In the preparation of the positively charged buffer, in the mixed monomer solution, the weight ratio of acrylamide, dimethyldiallyl ammonium chloride, and 3-acryloylpropyltrimethylammonium chloride is 2.3-2.5:0.6-0.7:0.5-0.6; The added weight of ammonium persulfate in the ammonium persulfate solution is 1.7-2 wt % of the total weight of the mixed monomers in the mixed monomer solution.

[0032] The method for preparing the positively charged composite sustained-release liquid is to uniformly mix the modified composite nanofiber dispersion, the positively charged buffer solution, and the amphoteric high molecular weight polyacrylamide (molecular weight 1 million to 5 million) at a weight ratio of 1-1.2:1-1.2:2.9-3.1 to obtain the positively charged composite sustained-release liquid.

[0033] The method for preparing the filler particle suspension comprises: adding ground calcium carbonate GCC into deionized water, stirring evenly, and obtaining a ground calcium carbonate dispersion with a mass concentration of 30-33wt%; adding a positively charged composite sustained-release liquid to the ground calcium carbonate dispersion under stirring conditions at room temperature, stirring evenly, and obtaining a filler particle suspension.

[0034] In the preparation of the filler particle suspension, the added weight of the positively charged composite sustained-release liquid is 0.1-2% by weight of the ground calcium carbonate in the ground calcium carbonate dispersion; preferably 0.3-1.2 wt %.

[0035] The mixed papermaking method comprises: mixing the papermaking pulp and the filler particle suspension evenly according to the absolute dry weight ratio of filler (ground calcium carbonate) to papermaking pulp of 30-50%:50-70%, diluting the concentration of the mixed paper stock to 1-2wt%, adding a retention agent, and then papermaking on a machine to obtain base paper sheets.

[0036] In the mixed papermaking, the retention aid is cationic starch, and the addition amount of the retention aid is 0.8-1wt% (based on the weight of the absolute dry pulp).

[0037] The method for improving the filler content and distribution uniformity in paper sheets and increasing the strength of paper sheets of the present invention comprises the following steps: in a pre-compounding step of preparing a modified composite nanofiber dispersion, a nanofiber dispersion containing carboxymethyl cellulose nanofibers is contacted with a zinc nitrate aqueous solution in an in-situ composite manner to adsorb zinc ions to the carboxymethyl cellulose nanofibers, and then the nanofiber dispersion is continuously contacted with a 2-methylimidazole solution to composite ZIF-8 in an in-situ composite manner to obtain composite nanofibers; then in a modification step, a positively charged modifying liquid containing dimethyldiallylammonium chloride is used to treat the composite nanofibers to obtain a modified composite nanofiber dispersion; in the process of contacting the modified composite nanofiber dispersion with the filler, the high specific surface and high porosity characteristics of ZIF-8 are used to composite with the carboxymethyl cellulose nanofibers to form a porous network structure, and the ZIF-8 is uniformly dispersed in the paper pulp to provide more binding sites for the filler; at the same time, the positively charged modification further improves the dispersion uniformity of the modified composite nanofibers, and at the same time improves the bonding performance between the filler and the modified composite nanofibers, thereby improving the filler content and distribution uniformity. In the step of preparing the positive charge buffer, dimethyldiallylammonium chloride and 3-acryloylpropyltrimethylammonium chloride are used in combination, and in the presence of an initiator, they are contacted with acrylamide for free radical copolymerization to obtain a medium molecular weight cationic modified polyacrylamide polymer (i.e., positive charge buffer). In the step of preparing the positive charge composite sustained-release liquid, a modified composite nanofiber dispersion, a positive charge buffer, and an amphoteric high molecular weight polyacrylamide are mixed to obtain a gradient positive charge composite sustained-release liquid containing small molecular weight, medium molecular weight, and high molecular weight (i.e., positive charge composite sustained-release liquid). In the preparation of the filler particle suspension, the ground calcium carbonate GCC is contacted with the positively charged composite slow-release liquid. The modified composite nanofibers in the positively charged composite slow-release liquid are positively charged and have a small molecular weight, and can flocculate with the negatively charged filler particles more gently. At the same time, the combination of the cationic modified polyacrylamide polymer with a medium molecular weight can effectively buffer the flocculation speed of the high molecular weight polyacrylamide and the filler particles, effectively avoiding the formation of super large flocs, and thus obtaining uniform filler flocs; at the same time, the modified composite nanofibers have the characteristics of large specific surface area, many chemical bonds, high surface energy, and high activity, and have a strong binding force with the filler and pulp fiber, and can form a more solid fiber network structure, thereby effectively improving the strength of the paper sheet. Furthermore, the medium molecular weight cationic modified polyacrylamide polymer (i.e., the positively charged buffer) has a stronger positive charge and a larger molecular weight than the modified composite nanofibers, and can achieve a further buffering effect on its basis.Further, in the mixed papermaking step, during the mixed papermaking process of the papermaking pulp and the filler particle suspension, a gradient positive charge composite slow-release liquid of small molecular weight modified composite nanofibers, medium molecular weight cationic modified polyacrylamide polymers, and high molecular weight polyacrylamide is used, wherein the modified composite nanofibers are more flexible and mobile due to their small molecular weight characteristics, and can preferentially contact with the filler particles, weaken the negative charge of the filler particles, and buffer the flocculation of the filler particles and the high molecular weight polyacrylamide, and can effectively control the size of the filler flocs and their uniform distribution in the papermaking pulp, improve the Z-direction distribution uniformity of the cellulose fibers and the filler flocs in the paper, increase the filler content in the paper sheet, and simultaneously improve the strength of the paper sheet under the condition of high filler content. The aforementioned technical means cooperate with each other and work synergistically, and can gently and effectively control the filler flocculation speed, controllably adjust the floc size, and can improve the uniformity of the distribution of the filler in the paper sheet while increasing the filler content in the paper sheet, and effectively avoid the adverse effects of the increase in the amount of filler on the mechanical properties of the paper sheet, and further improve the strength of the paper sheet.

[0038] The present invention is further described below in conjunction with some specific embodiments.

[0039] Example 1 A method for increasing filler content and distribution uniformity in paper sheets and increasing paper sheet strength, comprising the following steps: 1. Preparation of modified composite nanofiber dispersion (1) Pre-compounding Carboxymethyl cellulose nanofibers were put into deionized water and ultrasonically dispersed for 20 minutes to obtain a nanofiber dispersion with a mass concentration of 2.9wt%. Under room temperature stirring conditions, a 0.2mol / L zinc nitrate aqueous solution was added dropwise to the nanofiber dispersion. After the addition was completed, stirring was continued for 20 minutes. Then, the temperature was raised to 35°C, and a 0.4mol / L 2-methylimidazole aqueous solution was added dropwise while being kept warm and stirred. The dropping rate of the 2-methylimidazole aqueous solution was controlled to be 0.4mL / min. After the addition of the 2-methylimidazole aqueous solution was completed, the solution was kept warm and stirred for 10 hours, and then allowed to stand for 6 hours. Then, solid matter was obtained by centrifugation, and the solid matter was washed with deionized water and dried to obtain composite nanofibers.

[0040] The weight ratio of the carboxymethyl cellulose nanofibers in the nanofiber dispersion to the zinc nitrate in the zinc nitrate aqueous solution is 5:1.

[0041] The molar ratio of zinc nitrate in the zinc nitrate aqueous solution to 2-methylimidazole in the 2-methylimidazole aqueous solution is 1:4.

[0042] The diameter of carboxymethyl cellulose nanofibers is 70 nm.

[0043] (2) Modification treatment The composite nanofibers are added into deionized water and stirred evenly to obtain a composite nanofiber dispersion with a mass concentration of 8wt% for standby use; dimethyldiallylammonium chloride is added into deionized water and stirred evenly to obtain a positively charged modified liquid with a mass concentration of 11wt% for standby use; at room temperature, under stirring conditions of 200rpm, the positively charged modified liquid is added dropwise to the composite nanofiber dispersion at a dropping rate of 0.9mL / min; after the positively charged modified liquid is added dropwise, stirring is continued at room temperature for 4h to obtain a modified composite nanofiber dispersion.

[0044] The weight ratio of the composite nanofibers in the composite nanofiber dispersion to the dimethyldiallylammonium chloride in the positively charged modifying solution is 1:0.28.

[0045] 2. Preparation of positively charged buffer Add acrylamide, dimethyldiallyl ammonium chloride and 3-acryloyltrimethylammonium chloride into deionized water, stir evenly, and obtain a mixed monomer solution with a total mass concentration of 10wt% of monomers (acrylamide, dimethyldiallyl ammonium chloride and 3-acryloyltrimethylammonium chloride) for standby use; add ammonium persulfate into deionized water, stir evenly, and obtain an ammonium persulfate solution with a mass concentration of 1wt%, and set aside; add the mixed monomer solution and the ammonium persulfate solution into a reactor, heat to 55°C with stirring at 150rpm, and keep stirring for 3h to obtain a positively charged buffer solution.

[0046] Wherein, in the mixed monomer solution, the weight ratio of acrylamide, dimethyldiallylammonium chloride and 3-acryloylpropyltrimethylammonium chloride is 2.3:0.6:0.5.

[0047] The added weight of ammonium persulfate in the ammonium persulfate solution is 1.7 wt % of the total weight of the mixed monomers in the mixed monomer solution.

[0048] 3. Preparation of positively charged composite sustained-release solution The modified composite nanofiber dispersion, the positively charged buffer solution, and the amphoteric high molecular weight polyacrylamide (molecular weight 5 million) were uniformly mixed at a weight ratio of 1:1:2.9 to obtain a positively charged composite sustained-release solution.

[0049] 4. Preparation of filler particle suspension The ground calcium carbonate GCC is added into deionized water and stirred evenly to obtain a ground calcium carbonate dispersion with a mass concentration of 30wt%; under room temperature stirring conditions, the positively charged composite sustained-release liquid is added into the ground calcium carbonate dispersion and stirred evenly to obtain a filler particle suspension.

[0050] The added weight of the positively charged composite sustained-release liquid is 0.3 wt % of the weight of the ground calcium carbonate in the ground calcium carbonate dispersion.

[0051] 5. Mixed papermaking The papermaking pulp and the filler particle suspension are evenly mixed in an absolute dry weight ratio of filler (ground calcium carbonate) to papermaking pulp of 35%:65%, and the concentration of the mixed paper stock is diluted to 1.5wt%, and after adding a retention aid, the base paper sheet is obtained by papermaking on a machine.

[0052] The retention aid is cationic starch, and the amount of the retention aid added is 0.9wt% (based on the weight of the absolute dry slurry).

[0053] Example 2 A method for increasing filler content and distribution uniformity in paper sheets and increasing paper sheet strength, comprising the following steps: 1. Preparation of modified composite nanofiber dispersion (1) Pre-compounding Carboxymethyl cellulose nanofibers were put into deionized water and ultrasonically dispersed for 25 minutes to obtain a nanofiber dispersion with a mass concentration of 3.1wt%; a 0.25mol / L zinc nitrate aqueous solution was added dropwise to the nanofiber dispersion under stirring at room temperature, and stirring was continued for 30 minutes after the addition was completed; the temperature was then raised to 37°C with stirring, and a 0.5mol / L 2-methylimidazole aqueous solution was added dropwise with stirring, and the dropping rate of the 2-methylimidazole aqueous solution was controlled to be 0.45mL / min; after the addition of the 2-methylimidazole aqueous solution was completed, the solution was stirred for 11 hours and then allowed to stand for 7 hours; solid matter was then obtained by centrifugation, and the solid matter was washed with deionized water and dried to obtain composite nanofibers.

[0054] The weight ratio of the carboxymethyl cellulose nanofibers in the nanofiber dispersion to the zinc nitrate in the zinc nitrate aqueous solution is 5.2:1.

[0055] The molar ratio of zinc nitrate in the zinc nitrate aqueous solution to 2-methylimidazole in the 2-methylimidazole aqueous solution is 1:4.1.

[0056] The diameter of carboxymethyl cellulose nanofibers is 70 nm.

[0057] (2) Modification treatment The composite nanofibers are added into deionized water and stirred evenly to obtain a composite nanofiber dispersion with a mass concentration of 8.2wt% for standby use; dimethyldiallylammonium chloride is added into deionized water and stirred evenly to obtain a positively charged modified liquid with a mass concentration of 11.5wt% for standby use; at room temperature, under stirring conditions of 250rpm, the positively charged modified liquid is added dropwise to the composite nanofiber dispersion at a dropping rate of 0.95mL / min; after the addition of the positively charged modified liquid is completed, stirring is continued at room temperature for 4.5h to obtain a modified composite nanofiber dispersion.

[0058] The weight ratio of the composite nanofibers in the composite nanofiber dispersion to the dimethyldiallylammonium chloride in the positively charged modifying solution is 1:0.29.

[0059] 2. Preparation of positively charged buffer Add acrylamide, dimethyldiallyl ammonium chloride and 3-acryloylpropyltrimethylammonium chloride into deionized water, stir evenly, and obtain a mixed monomer solution with a total mass concentration of 11wt% of monomers (acrylamide, dimethyldiallyl ammonium chloride and 3-acryloylpropyltrimethylammonium chloride) for standby use; add ammonium persulfate into deionized water, stir evenly, and obtain an ammonium persulfate solution with a mass concentration of 1.1wt%, and set aside; add the mixed monomer solution and the ammonium persulfate solution into a reactor, heat to 58°C with stirring at 200rpm, and keep stirring for 3.5h to obtain a positively charged buffer solution.

[0060] Wherein, in the mixed monomer solution, the weight ratio of acrylamide, dimethyldiallylammonium chloride and 3-acryloylpropyltrimethylammonium chloride is 2.4:0.65:0.55.

[0061] The added weight of ammonium persulfate in the ammonium persulfate solution is 1.8 wt % of the total weight of the mixed monomers in the mixed monomer solution.

[0062] 3. Preparation of positively charged composite sustained-release solution The modified composite nanofiber dispersion, the positively charged buffer solution, and the amphoteric high molecular weight polyacrylamide (molecular weight 5 million) were uniformly mixed at a weight ratio of 1.1:1.1:3 to obtain a positively charged composite sustained-release solution.

[0063] 4. Preparation of filler particle suspension The ground calcium carbonate GCC was added into deionized water and stirred evenly to obtain a ground calcium carbonate dispersion with a mass concentration of 31wt%; under room temperature stirring conditions, the positively charged composite sustained-release liquid was added into the ground calcium carbonate dispersion and stirred evenly to obtain a filler particle suspension.

[0064] The added weight of the positively charged composite sustained-release liquid is 0.8 wt % of the weight of the ground calcium carbonate in the ground calcium carbonate dispersion.

[0065] 5. Mixed papermaking The papermaking pulp and the filler particle suspension are evenly mixed in an absolute dry weight ratio of filler (ground calcium carbonate) to papermaking pulp of 45%:55%, and the concentration of the mixed paper stock is diluted to 1.5wt%. After adding a retention aid, the base paper is sheeted on a machine.

[0066] The retention aid is cationic starch, and the amount of the retention aid added is 0.9wt% (based on the weight of the absolute dry slurry).

[0067] Example 3 A method for increasing filler content and distribution uniformity in paper sheets and increasing paper sheet strength, comprising the following steps: 1. Preparation of modified composite nanofiber dispersion (1) Pre-compounding Carboxymethyl cellulose nanofibers were put into deionized water and ultrasonically dispersed for 30 minutes to obtain a nanofiber dispersion with a mass concentration of 3.1wt%; a 0.25mol / L zinc nitrate aqueous solution was added dropwise to the nanofiber dispersion under stirring at room temperature, and after the addition was completed, stirring was continued for 40 minutes; then the temperature was raised to 40°C with stirring, and a 0.5mol / L 2-methylimidazole aqueous solution was added dropwise with stirring, and the dropping rate of the 2-methylimidazole aqueous solution was controlled to be 0.5mL / min; after the addition of the 2-methylimidazole aqueous solution was completed, the solution was stirred for 12 hours and then allowed to stand for 7 hours; then solid matter was obtained by centrifugation, and the solid matter was washed with deionized water and dried to obtain composite nanofibers.

[0068] The weight ratio of the carboxymethyl cellulose nanofibers in the nanofiber dispersion to the zinc nitrate in the zinc nitrate aqueous solution is 5.3:1.

[0069] The molar ratio of zinc nitrate in the zinc nitrate aqueous solution to 2-methylimidazole in the 2-methylimidazole aqueous solution is 1:4.1.

[0070] The diameter of carboxymethyl cellulose nanofibers is 70 nm.

[0071] (2) Modification treatment The composite nanofibers are added into deionized water and stirred evenly to obtain a composite nanofiber dispersion with a mass concentration of 8.2wt% for standby use; dimethyldiallylammonium chloride is added into deionized water and stirred evenly to obtain a positively charged modified liquid with a mass concentration of 11.5wt% for standby use; at room temperature, under stirring conditions of 250rpm, the positively charged modified liquid is added dropwise to the composite nanofiber dispersion at a dropping rate of 1mL / min; after the addition of the positively charged modified liquid is completed, stirring is continued at room temperature for 5h to obtain a modified composite nanofiber dispersion.

[0072] The weight ratio of the composite nanofibers in the composite nanofiber dispersion to the dimethyldiallylammonium chloride in the positively charged modifying solution is 1:0.3.

[0073] 2. Preparation of positively charged buffer Add acrylamide, dimethyldiallyl ammonium chloride and 3-acryloyltrimethylammonium chloride into deionized water, stir evenly, and obtain a mixed monomer solution with a total mass concentration of 11wt% of monomers (acrylamide, dimethyldiallyl ammonium chloride and 3-acryloyltrimethylammonium chloride) for standby use; add ammonium persulfate into deionized water, stir evenly, and obtain an ammonium persulfate solution with a mass concentration of 1.2wt%, and set aside; add the mixed monomer solution and the ammonium persulfate solution into a reactor, heat to 60°C with stirring at 250rpm, and keep stirring for 3.5h to obtain a positively charged buffer solution.

[0074] Wherein, in the mixed monomer solution, the weight ratio of acrylamide, dimethyldiallylammonium chloride and 3-acryloylpropyltrimethylammonium chloride is 2.4:0.65:0.6.

[0075] The added weight of ammonium persulfate in the ammonium persulfate solution is 1.9 wt % of the total weight of the mixed monomers in the mixed monomer solution.

[0076] 3. Preparation of positively charged composite sustained-release solution The modified composite nanofiber dispersion, the positively charged buffer solution, and the amphoteric high molecular weight polyacrylamide (molecular weight 5 million) were uniformly mixed at a weight ratio of 1.2:1.2:3 to obtain a positively charged composite sustained-release solution.

[0077] 4. Preparation of filler particle suspension The ground calcium carbonate GCC is added into deionized water and stirred evenly to obtain a ground calcium carbonate dispersion with a mass concentration of 32wt%; under room temperature stirring conditions, the positively charged composite sustained-release liquid is added into the ground calcium carbonate dispersion and stirred evenly to obtain a filler particle suspension.

[0078] The added weight of the positively charged composite sustained-release liquid is 1 wt % of the weight of the ground calcium carbonate in the ground calcium carbonate dispersion.

[0079] 5. Mixed papermaking The papermaking pulp and the filler particle suspension are evenly mixed in an absolute dry weight ratio of filler (ground calcium carbonate) to papermaking pulp of 45%:55%, and the concentration of the mixed paper stock is diluted to 1.5wt%. After adding a retention aid, the base paper is sheeted on a machine.

[0080] The retention aid is cationic starch, and the amount of the retention aid added is 0.9wt% (based on the weight of the absolute dry slurry).

[0081] Example 4 A method for increasing filler content and distribution uniformity in paper sheets and increasing paper sheet strength, comprising the following steps: 1. Preparation of modified composite nanofiber dispersion (1) Pre-compounding Carboxymethyl cellulose nanofibers were put into deionized water and ultrasonically dispersed for 30 minutes to obtain a nanofiber dispersion with a mass concentration of 3.3wt%; a 0.3mol / L zinc nitrate aqueous solution was added dropwise to the nanofiber dispersion under room temperature stirring conditions, and after the addition was completed, stirring was continued for 40 minutes; then the temperature was raised to 40°C with stirring, and a 0.6mol / L 2-methylimidazole aqueous solution was added dropwise with stirring, and the dropping rate of the 2-methylimidazole aqueous solution was controlled to be 0.5mL / min; after the addition of the 2-methylimidazole aqueous solution was completed, the solution was stirred for 12 hours and then allowed to stand for 8 hours; then solid matter was obtained by centrifugation, and the solid matter was washed with deionized water and dried to obtain composite nanofibers.

[0082] The weight ratio of the carboxymethyl cellulose nanofibers in the nanofiber dispersion to the zinc nitrate in the zinc nitrate aqueous solution is 5.5:1.

[0083] The molar ratio of zinc nitrate in the zinc nitrate aqueous solution to 2-methylimidazole in the 2-methylimidazole aqueous solution is 1:4.2.

[0084] The diameter of carboxymethyl cellulose nanofibers is 100 nm.

[0085] (2) Modification treatment The composite nanofibers are added into deionized water and stirred evenly to obtain a composite nanofiber dispersion with a mass concentration of 8.5wt% for standby use; dimethyldiallylammonium chloride is added into deionized water and stirred evenly to obtain a positively charged modified liquid with a mass concentration of 12wt% for standby use; at room temperature, under stirring conditions of 300rpm, at a dropping rate of 1mL / min, the positively charged modified liquid is added dropwise to the composite nanofiber dispersion; after the addition of the positively charged modified liquid is completed, stirring is continued at room temperature for 5h to obtain a modified composite nanofiber dispersion.

[0086] The weight ratio of the composite nanofibers in the composite nanofiber dispersion to the dimethyldiallylammonium chloride in the positively charged modifying solution is 1:0.31.

[0087] 2. Preparation of positively charged buffer Add acrylamide, dimethyldiallyl ammonium chloride and 3-acryloylpropyltrimethylammonium chloride into deionized water, stir evenly, and obtain a mixed monomer solution with a total mass concentration of 12wt% of monomers (acrylamide, dimethyldiallyl ammonium chloride and 3-acryloylpropyltrimethylammonium chloride) for standby use; add ammonium persulfate into deionized water, stir evenly, and obtain an ammonium persulfate solution with a mass concentration of 1.2wt%, and set aside; add the mixed monomer solution and the ammonium persulfate solution into a reactor, heat to 60°C with stirring at 250rpm, and keep stirring for 4h to obtain a positively charged buffer solution.

[0088] Wherein, in the mixed monomer solution, the weight ratio of acrylamide, dimethyldiallylammonium chloride and 3-acryloylpropyltrimethylammonium chloride is 2.5:0.7:0.6.

[0089] The added weight of ammonium persulfate in the ammonium persulfate solution is 2 wt % of the total weight of the mixed monomers in the mixed monomer solution.

[0090] 3. Preparation of positively charged composite sustained-release solution The modified composite nanofiber dispersion, the positively charged buffer solution, and the amphoteric high molecular weight polyacrylamide (molecular weight 5 million) were uniformly mixed at a weight ratio of 1.2:1.2:3.1 to obtain a positively charged composite sustained-release solution.

[0091] 4. Preparation of filler particle suspension The ground calcium carbonate GCC is added into deionized water and stirred evenly to obtain a ground calcium carbonate dispersion with a mass concentration of 33wt%; under room temperature stirring conditions, the positively charged composite sustained-release liquid is added into the ground calcium carbonate dispersion and stirred evenly to obtain a filler particle suspension.

[0092] The added weight of the positively charged composite sustained-release liquid is 1.2 wt % of the weight of the ground calcium carbonate in the ground calcium carbonate dispersion.

[0093] 5. Mixed papermaking The papermaking pulp and the filler particle suspension are evenly mixed according to the absolute dry weight ratio of filler (ground calcium carbonate) to papermaking pulp of 50%:50%, and the concentration of the paper stock obtained after mixing is diluted to 2wt%. After adding a retention aid, the base paper sheet is obtained by papermaking on a machine.

[0094] The retention aid is cationic starch, and the amount of the retention aid added is 1 wt% (based on the weight of the absolute dry slurry).

[0095] Comparative Example 1 The technical solution of Example 2 is adopted, but the difference lies in that: the step of preparing the modified composite nanofiber dispersion is omitted; and the addition of the modified composite nanofiber dispersion in the step of preparing the positively charged composite sustained-release solution is omitted.

[0096] Comparative Example 2 The technical solution of Example 2 is adopted, but the difference is that the pre-compounding step in the modified composite nanofiber dispersion is omitted.

[0097] Coniferous wood pulp, thermally bleached chemical mechanical pulp and bleached hardwood pulp were used as raw materials to prepare papermaking pulp in a weight ratio of 1:3:6; the technical schemes of Examples 1-4 and Comparative Examples 1-2 were respectively adopted, and in the mixed papermaking step, the absolute dry weight ratio of filler (ground calcium carbonate) to papermaking pulp was uniformly controlled at 35%:65%, the papermaking pulp and the filler particle suspension were uniformly mixed, the concentration of the mixed paper stock was diluted to 1.5wt%, and after adding a retention aid (the addition amount was 0.9wt%), the papermaking was respectively put on a machine to have a basis weight of 180g / m 2 white cardboard.

[0098] The bursting index, Taber stiffness, transverse folding resistance and ash content of white cardboard were tested respectively. Among them, the bursting index test reference standard GB / T 454-2020 "Determination of bursting resistance of paper"; the Taber stiffness test reference standard GB / T22806-2008 "White cardboard"; the transverse folding resistance test reference GB / T 457-2008 "Determination of folding resistance of paper and paperboard"; the ash content test reference GB / T 742-2018 "Determination of burning residue (ash) of papermaking raw materials, pulp, paper and paperboard". The specific results are shown in the following table:

[0099] Furthermore, coniferous wood pulp, thermally bleached chemical mechanical pulp and bleached broadleaf wood pulp were used as raw materials to prepare papermaking pulp in a weight ratio of 1:3:6; the technical schemes of Examples 1-4 and Comparative Examples 1-2 were respectively adopted, and in the mixed papermaking step, the absolute dry weight ratio of filler (ground calcium carbonate) to papermaking pulp was uniformly controlled at 45%:55%, the papermaking pulp and the filler particle suspension were uniformly mixed, the concentration of the paper stock obtained after mixing was diluted to 1.5wt%, and after adding a retention aid (the addition amount was 1wt%), the papermaking was respectively put on a machine to have a basis weight of 180g / m 2 The bursting index, Taber stiffness, transverse folding resistance and ash content of the white cardboard were tested according to the above methods. The specific results are shown in the following table:

[0100] It can be seen that in the steps of preparing the filler particle suspension in Examples 1-4, the weight of the positively charged composite sustained-release liquid added is 0.3wt%, 0.8wt%, 1.0wt%, and 1.2wt% of the weight of the ground calcium carbonate in the ground calcium carbonate dispersion, respectively. The final papermaking weight is 180g / m 2The bursting index, Taber stiffness, transverse folding endurance and ash content of the white cardboard increase successively with the increase of the added amount of the cationic composite slow-release liquid; and according to the changes in each test index, it can be seen that the more preferred addition range of the cationic composite slow-release liquid is 0.8-1.2wt%; within this addition range, the bursting index, Taber stiffness, transverse folding endurance and ash content of the white cardboard can be significantly improved.

[0101] After the modified composite nanofiber dispersion step is omitted in Comparative Example 1, the positively charged composite sustained-release liquid lacks the mobility of the small molecular weight modified composite nanofibers, cannot pre-contact the filler particles and weaken their negative charge, cannot effectively buffer the flocculation process of the filler particles, and the filler floc size and distribution uniformity in the slurry are significantly deteriorated. The Z-direction distribution uniformity of cellulose fibers and filler flocs in the paper cannot be effectively improved, and the adverse effects of high-content fillers on the mechanical properties of paper sheets cannot be effectively avoided. Specifically, the burst index, Taber stiffness, and transverse folding endurance of the white cardboard are significantly deteriorated compared with those in Example 2.

[0102] Comparative Example 2 omits the pre-compounding step in the modified composite nanofiber dispersion; the small molecular weight modified composite nanofiber cannot increase the binding sites with the filler particles through the composite synergistic effect of ZIF-8 and carboxymethyl cellulose nanofibers, nor can it further improve the binding performance of the filler and the modified composite nanofiber, and cannot improve the filler content and distribution uniformity. Specifically, the bursting index, Taber stiffness, and transverse folding endurance of the white cardboard are all deteriorated to a certain extent compared with Example 2.

[0103] Furthermore, coniferous wood pulp, thermally bleached chemical mechanical pulp and bleached hardwood pulp were used as raw materials to prepare papermaking pulp in a weight ratio of 1:3:6; the technical schemes of Examples 1-4 and Comparative Examples 1-2 were respectively adopted, and in the mixed papermaking step, the absolute dry weight ratio of filler (ground calcium carbonate) to papermaking pulp was uniformly controlled at 35%:65%, the papermaking pulp and the filler particle suspension were uniformly mixed, the concentration of the paper stock obtained after mixing was diluted to 2wt%, and after adding a retention aid (the addition amount was 0.9wt%), the papermaking was respectively put on a machine to have a basis weight of 70g / m 2 of offset paper.

[0104] The tensile index, transverse folding resistance, printed surface strength and ash content of offset paper were tested respectively. Among them, the tensile strength test refers to GB / T 12914-2018 "Determination of tensile strength of paper and paperboard - Constant tension method (20mm / min)"; the transverse folding test refers to GB / T 457-2008 "Determination of folding resistance of paper and paperboard"; the printed surface strength test refers to GB / T 22365-2008 "Determination of printed surface strength of paper and paperboard"; the ash test refers to GB / T 742-2018 "Determination of burning residue (ash) of papermaking raw materials, pulp, paper and paperboard". The specific results are shown in the following table:

[0105] Furthermore, coniferous wood pulp, thermally bleached chemical mechanical pulp and bleached hardwood pulp were used as raw materials to prepare papermaking pulp in a weight ratio of 1:3:6; the technical schemes of Examples 1-4 and Comparative Examples 1-2 were respectively adopted, and in the mixed papermaking step, the absolute dry weight ratio of filler (ground calcium carbonate) to papermaking pulp was uniformly controlled at 45%:55%, the papermaking pulp and the filler particle suspension were uniformly mixed, the concentration of the mixed paper stock was diluted to 2wt%, and after adding a retention aid (the addition amount was 1wt%), the papermaking was respectively put on a machine to have a basis weight of 70g / m 2 The offset paper. According to the above method, the tensile index, transverse folding endurance, printing surface strength and ash content of the offset paper were tested respectively. The specific results are shown in the following table:

[0106] It can be seen that in the steps of preparing the filler particle suspension in Examples 1-4, the weight of the positively charged composite sustained-release liquid added is 0.3wt%, 0.8wt%, 1.0wt%, and 1.2wt% of the weight of the ground calcium carbonate in the ground calcium carbonate dispersion, respectively. The final papermaking weight is 70g / m 2 The bursting index, Taber stiffness, transverse folding endurance and ash content of the offset paper increase successively with the increase of the addition amount of the positively charged composite slow-release liquid; and according to the changes in each test index, it can be seen that the more preferred addition range of the positively charged composite slow-release liquid is 0.8-1.2wt%. Within this addition range, the tensile index, transverse folding endurance, printing surface strength and ash content of the offset paper can be significantly improved.

[0107] After the modified composite nanofiber dispersion step is omitted in Comparative Example 1, the positively charged composite sustained-release liquid lacks the mobility of the small molecular weight modified composite nanofibers, cannot pre-contact the filler particles and weaken their negative charge, cannot effectively buffer the flocculation process of the filler particles, and the filler floc size and distribution uniformity in the slurry are significantly deteriorated. The Z-direction distribution uniformity of the cellulose fibers and filler flocs in the paper cannot be effectively improved, and the adverse effects of high-content fillers on the mechanical properties of the paper sheets cannot be effectively avoided. Specifically, the burst index, Taber stiffness, and transverse folding endurance of the offset paper are significantly deteriorated compared with those in Example 2.

[0108] Comparative Example 2 omits the pre-compounding step in the modified composite nanofiber dispersion; the small molecular weight modified composite nanofiber cannot increase the binding sites with the filler particles through the composite synergistic effect of ZIF-8 and carboxymethyl cellulose nanofibers, nor can it further improve the binding performance of the filler and the modified composite nanofibers, and cannot improve the filler content and distribution uniformity. Specifically, the bursting index, Taber stiffness, and transverse folding endurance of the offset paper are all deteriorated to a certain extent compared with Example 2.

[0109] Unless otherwise specified, all percentages used in the present invention are by mass.

[0110] Finally, it should be noted that the above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art can still modify the technical solutions described in the aforementioned embodiments or replace some of the technical features therein by equivalents. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present invention shall be included in the protection scope of the present invention.

Claims

1. A method for increasing filler content and distribution uniformity in paper sheets and increasing paper sheet strength, characterized in that: The method comprises the following steps: preparing a modified composite nanofiber dispersion, preparing a positively charged buffer solution, preparing a positively charged composite slow-release solution, preparing a filler particle suspension, and mixing and papermaking; The preparation of the modified composite nanofiber dispersion comprises the following steps: pre-compounding and modification treatment; The pre-compounding comprises dispersing carboxymethyl cellulose nanofibers in deionized water to obtain a nanofiber dispersion; dropping a zinc nitrate aqueous solution into the nanofiber dispersion, and dropping a 2-methylimidazole aqueous solution at a temperature of 35-40° C.; keeping the mixture warm for reaction, allowing the mixture to stand, separating and obtaining a solid, and washing and drying the solid to obtain composite nanofibers; In the modification treatment, the composite nanofibers are treated with a positively charged modification liquid to obtain a modified composite nanofiber dispersion; The positively charged modification liquid is an aqueous solution of dimethyldiallylammonium chloride; In the preparation of the positively charged buffer, acrylamide, dimethyldiallyl ammonium chloride, and 3-acryloylpropyltrimethylammonium chloride are reacted at elevated temperature in the presence of an initiator to obtain a positively charged buffer; The method for preparing the positively charged composite sustained-release liquid comprises uniformly mixing the modified composite nanofiber dispersion, the positively charged buffer solution and the amphoteric high molecular weight polyacrylamide to obtain the positively charged composite sustained-release liquid.

2. The method for increasing filler content and distribution uniformity in paper sheets and increasing paper sheet strength according to claim 1, characterized in that: The filler particle suspension is prepared by adding ground calcium carbonate into deionized water to obtain a ground calcium carbonate dispersion; and the positively charged composite slow-release liquid is added to the ground calcium carbonate dispersion to obtain a filler particle suspension; In the mixed papermaking, the papermaking pulp and the filler particle suspension are uniformly mixed and then diluted, and a retention agent is added before papermaking to obtain base paper.

3. The method for increasing filler content and distribution uniformity in paper sheets and increasing paper sheet strength according to claim 1, characterized in that: In the pre-compounding, the mass concentration of the nanofiber dispersion is 2.9-3.3wt%; The concentration of zinc nitrate aqueous solution is 0.2-0.3 mol / L; The concentration of 2-methylimidazole aqueous solution is 0.4-0.6 mol / L; The heat preservation reaction time is 10-12h, and the standing time is 6-8h.

4. The method for increasing filler content and distribution uniformity in paper sheets and increasing paper sheet strength according to claim 1, characterized in that: In the pre-compounding, the weight ratio of the carboxymethyl cellulose nanofibers in the nanofiber dispersion to the zinc nitrate in the zinc nitrate aqueous solution is 5-5.5:1; The molar ratio of zinc nitrate in the zinc nitrate aqueous solution to 2-methylimidazole in the 2-methylimidazole aqueous solution is 1:4-4.

2.

5. The method for increasing filler content and distribution uniformity in paper sheets and increasing paper sheet strength according to claim 1, characterized in that: The modification method is to disperse the composite nanofibers in deionized water to obtain a composite nanofiber dispersion with a mass concentration of 8-8.5wt%; then drop a positively charged modification liquid with a mass concentration of 11-12wt% and obtain a modified composite nanofiber dispersion after treatment at room temperature.

6. The method for increasing filler content and distribution uniformity in paper sheets and increasing paper sheet strength according to claim 5, characterized in that: In the modification treatment, the room temperature treatment time is 4-5h; The weight ratio of the composite nanofibers in the composite nanofiber dispersion to the dimethyldiallylammonium chloride in the positively charged modification liquid is 1:0.28-0.

31.

7. The method for increasing filler content and distribution uniformity in paper sheets and increasing paper sheet strength according to claim 1, characterized in that: The method for preparing the positively charged buffer comprises dispersing acrylamide, dimethyldiallylammonium chloride and 3-acryloylpropyltrimethylammonium chloride in deionized water to obtain a mixed monomer solution with a monomer mass concentration of 10-12 wt %, adding an initiator, and heating the solution to obtain the positively charged buffer; In the mixed monomer solution, the weight ratio of acrylamide, dimethyldiallylammonium chloride and 3-acryloylpropyltrimethylammonium chloride is 2.3-2.5:0.6-0.7:0.5-0.

6.

8. The method for increasing filler content and distribution uniformity in paper sheets and increasing paper sheet strength according to claim 1, characterized in that: In the preparation of the positively charged composite sustained-release liquid, the weight ratio of the modified composite nanofiber dispersion, the positively charged buffer solution, and the amphoteric high molecular weight polyacrylamide is 1-1.2:1-1.2:2.9-3.

1.

9. The method for increasing filler content and distribution uniformity in paper sheets and increasing paper sheet strength according to claim 2, characterized in that: In the preparation of the filler particle suspension, the mass concentration of the ground calcium carbonate dispersion is 30-33wt%; The added weight of the positive charge composite sustained-release liquid is 0.1-2% of the weight of the ground calcium carbonate in the ground calcium carbonate dispersion.

10. The method for increasing filler content and distribution uniformity in paper sheets and increasing paper sheet strength according to claim 2, characterized in that: In the mixed papermaking, the absolute dry weight ratio of the ground calcium carbonate in the filler particle suspension to the papermaking pulp is 30-50%:50-70%.

Citation Information

Patent Citations

  • Modified packing and preparation method thereof as well as papermaking technology adopting modified packing and paper

    CN103343480A

  • Method for improving optical performance of paper through composite structure of stuffing and fiber

    CN103938475A

  • High-branch-chain water-soluble cellulose-acrylamide grafted copolymer and preparation method and application thereof

    CN104086709A

  • Method for modifying papermaking stuffing by using cationic cellulose derivatives

    CN106758500A

  • Use of polymer product for deposit formation control in manufacture of paper or board

    CN109983177A

Cited By

  • Ternary wrapping aid as well as preparation method and application thereof

    CN120945717A

  • A ternary encapsulation additive for papermaking fillers, its preparation method and application

    CN120945717B